Tetramic Acids Mutanocyclin and Reutericyclin A, Produced by Streptococcus mutans Strain B04Sm5 Modulate the Ecology of an in vitro Oral Biofilm - Uranga, Carla; Nelson, Karen E.; Edlund, Anna; Baker, Jonathon L. (Frontiers in Oral Health, 2022)
The human oral microbiome consists of diverse microbes actively communicating and interacting through a variety of biochemical mechanisms. Dental caries, a major public health issue, is caused by dysbiosis of the oral microbiome. Streptococcus mutans is a known key contributor to caries pathogenesis, due to its exceptional ability to form biofilms in the presence of sucrose as well as its acidophilic lifestyle. S. mutans also kills competing organisms, which are typically health-associated, through production of bacteriocins and other small molecules. A subset of S. mutans strains encode the muc biosynthetic gene cluster (BGC), which was recently shown to produce the tetramic acids, mutanocyclin and reutericyclins A, B, and C. Reutericyclin A has strong antimicrobial activity and mutanocyclin appears to be anti-inflammatory, however the effect of these compounds, and the carriage of muc by S. mutans, on the ecology of the oral microbiota is not known, and was examined here by using a previously developed in vitro biofilm model derived from human saliva. While reutericyclin significantly inhibited in vitro biofilm formation and acid production at sub-nanomolar concentrations, mutanocyclin did not present any activity until the high micromolar range. 16S rRNA gene sequencing revealed that reutericyclin drastically altered the biofilm community structure, while mutanocyclin showed a more specific effect, reducing the relative abundance of cariogenic Limosilactobacillus fermentum. To address ecological effects of S. mutans strains producing both mutanocyclin and reutericyclin, reutericyclin only, or neither compound were added to the same in vitro biofilm community. It was difficult to interpret whether mutanocyclin or reutericyclin produced by the amended S. mutans strains affected the community. Any effects were likely subtle and masked by the differing growth rates of the S. mutans strains. Regardless of the strain added, addition of S. mutans to the in vitro community increased the relative abundance of L. fermentum and decreased the relative abundance of other streptococci. Overall, this study illustrates that reutericyclin A and mutanocyclin do impact a complex in vitro oral biofilm, however further research is needed to determine the extent that production of these compounds affects virulence of S. mutans.